2015
DOI: 10.1002/cncr.29731
|View full text |Cite
|
Sign up to set email alerts
|

Marital status, education, and income in relation to the risk of esophageal and gastric cancer by histological type and site

Abstract: Divorce, widowhood, living alone, low educational attainment, and low income increase the risk of each subtype of esophageal and gastric cancer. These associations require attention when high-risk individuals are being identified. Cancer 2016;122:207-212. © 2015 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
45
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 21 publications
8
45
2
3
Order By: Relevance
“…However, other studies reported no significant correlation between county-level income and survival [45] or an association only for patients with early stage disease [46]. Higher education level at the community level has also been identified as having a positive influence on survival [42, 47]; however, our analysis did not show that county-level economic status or education was significant independent prognostic factors. Finally, several studies found that race influenced prognosis for certain types of cancer (e.g., lung, liver, breast, and prostate) [48], whereas other studies found that the effect was minimal after adjusting for other socioeconomic factors [49], which is consistent with our results.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…However, other studies reported no significant correlation between county-level income and survival [45] or an association only for patients with early stage disease [46]. Higher education level at the community level has also been identified as having a positive influence on survival [42, 47]; however, our analysis did not show that county-level economic status or education was significant independent prognostic factors. Finally, several studies found that race influenced prognosis for certain types of cancer (e.g., lung, liver, breast, and prostate) [48], whereas other studies found that the effect was minimal after adjusting for other socioeconomic factors [49], which is consistent with our results.…”
Section: Discussioncontrasting
confidence: 89%
“…Although most studies suggested that personal income is related to cancer survival [41, 42], the impact of the regional economic environment (e.g., county-level median household income) remains controversial. Higher neighborhood income level has been associated with higher survival rates, which can be partially explained by differences in disease stage at presentation, first-line treatment, and comorbidities [41, 43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…The results were similar with previous researches investigating the associations between marital status and survival in breast, lung, colorectal, esophageal, and gastric cancers. 22, 23, 24, 25. While the mechanism underlying the improved survival associated with marriage in patients is not entirely clear, with the analyses from this study, the possible reasons for the unfavorable prognosis of unmarried patients, especially for widowed or divorced ones, are proposed as follows.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, it is the third leading cause of cancer-related death in both sexes worldwide [1]; in 2011, it accounted for 4% of cancer death [2]. The distribution of gastric cancer varies across geographical regions, which illustrates the multitude of factors that are associated with the incidence, survival, and mortality rates of the disease [3]; even marital status, low educational attainment, and low income increase the risk of gastric cancer [4]. In 2012, 70% of gastric cancer cases occurred in developing countries, and about half of them occurred in eastern Asia [35].…”
Section: Introductionmentioning
confidence: 99%